PHARMACOECONOMIC ANALYSIS OF CHRONIC HEART FAILURE DRUG THERAPY IN PATIENTS WITH COMORBID CONDITIONS - S. K. Zyryanov; A. E. Cheberda; D. Yu. Belousov (Рациональная фармакотерапия в кардиологии)
Aim. To perform pharmacoeconomic analysis of CHF therapy with supramolecular sacubitril/valsartan complex compared to routine therapy in patients with diabetes type 2 and ACE inhibitor intolerance within context of Russian healthcare system.Material and methods. A Markov model based on Russian Standards of treatment and clinical practice results was built. Cost-effectiveness analysis was done by comparing two patient groups of 1000 people each. Budget impact analysis required 27,451 simulated patients. Randomized controlled clinical trials results of sacubitril/valsartan vs. routine practice were used as source of efficacy and safety data. Time horizon was set at 3 years. Quality Adjusted Life Years (QALY) were used as effectiveness. Single-factor sensitivity analysis (SA) was used to ensure the results are robust to changes in market situation.Results. Cost-effectiveness ratio for sacubitril/valsartan is 301,145.7 rub. per QALY while cost-effectiveness ratio for routine practice is 510,621 rub. Budget impact analysis results indicate that during three years, in case of sacubitril/valsartan usage budgetary burden can be reduced by more than 220,000 rubles per patient and leads to savings of more than six billion rubles in terms of the whole population. Sensitivity analysis has confirmed the robustness of results.Conclusion. These results indicate benefits of sacubitril/valsartan using for CHF patients with type 2 diabetes and ACE inhibitor intolerance and justify inclusion of this drug into reimbursement lists that allow to reduce risk of hospitalization, lethal outcomes and budget of healthcare system.